2016
DOI: 10.1159/000442254
|View full text |Cite
|
Sign up to set email alerts
|

Inside-Out Signaling Pathways from Nuclear Reactive Oxygen Species Control Pulmonary Innate Immunity

Abstract: The airway mucosa is responsible for mounting a robust innate immune response (IIR) upon encountering pathogen-associated molecular patterns. The IIR produces protective gene networks that stimulate neighboring epithelia and components of the immune system to trigger adaptive immunity. Little is currently known about how cellular reactive oxygen species (ROS) signaling is produced and cooperates in the IIR. We discuss recent discoveries about 2 nuclear ROS signaling pathways controlling innate immunity. Nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 63 publications
1
37
0
Order By: Relevance
“…These pathways coordinate expression of highly inducible immediate early genes encoding secreted factors whose actions stimulate neighboring epithelia and components of the immune system to trigger dendritic cell activation and the downstream adaptive immune response (18,19). In response to nuclear ROS signals, coupled posttranslational modifications of RelA enable complex formation with P-TEFb, an event necessary for rapid transcriptional activation of immediate early genes (19,21,37). In this study, we investigate the requirement for and mechanism of BRD4 in controlling innate signaling downstream of the RIG-I and TLR3 PRRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pathways coordinate expression of highly inducible immediate early genes encoding secreted factors whose actions stimulate neighboring epithelia and components of the immune system to trigger dendritic cell activation and the downstream adaptive immune response (18,19). In response to nuclear ROS signals, coupled posttranslational modifications of RelA enable complex formation with P-TEFb, an event necessary for rapid transcriptional activation of immediate early genes (19,21,37). In this study, we investigate the requirement for and mechanism of BRD4 in controlling innate signaling downstream of the RIG-I and TLR3 PRRs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we previously observed that RSV-activated RelA binds to the IRF7 promoter and is required for IRF7 expression (11); that both RelA and IRF7 bind to the RIG-I promoter, potentiating RIG-I expression (10); and that RIG-I is required for sustained type I IFN expression using siRNA-mediated silencing (30). With IFN=s secondary effect on IRF1/7 upregulation, a positive regulatory loop is established, producing an antiviral response (10,11,37). The functional role of NF-B in IRF1-RIG-I amplification has not been systematically examined.…”
Section: Brd4 Is Functionally Required For Rsv-mediated Induction Of mentioning
confidence: 99%
“…This finding points to the prospect that mtDNA damage and repair could exert more complex actions governing the response to bacterial injury than initially anticipated. In this regard, Boldogh and colleagues demonstrated that free 8-oxoguanine, which is excised from oxidatively damaged DNA by Ogg1, forms a complex with the glycosylase to function as a guanine exchange factor activating Ras -dependent signaling, particularly those pathways driving innate immune responses (28). Importantly, 8-oxoguanine binds to Ogg1 at a site distinct from its DNA binding and repair domain of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced activation of innate inflammation has been demonstrated in children with bronchiolitis, where enhanced expression of IL-6, -8 and MIP-1β have been observed (16). Important to the pathogenesis of LRTI, the epithelium in the proximal conductive airways and the respiratory surface play functionally distinct roles in innate defenses (17, 18). Under normal conditions, inhaled pathogens are cleared via the mucociliary escalator from ciliated epithelial cells.…”
Section: Introductionmentioning
confidence: 99%